Pengaruh Konsentrasi Substrat Kulit Nanas dan Kecepatan Pengadukan terhadap Pertumbuhan Lactobacillus plantarum untuk Produksi Asam Laktat - Febriningrum, Panca Nugrahini (Jurnal Rekayasa Kimia & Lingkungan, 2013)
One of the alternative utilization of pineapple peel waste is to convert them to lactate acid via fermentation. This research is aimed to obtain better understanding on the growth of lactate bacteria (Lactobacillus plantarum) by varying substrate concentration: 100 g/L - 600 g/L and stirring rate of 50 rpm, 150 rpm, and 250 rpm. The growth of anaeroic process was performed without pH controlling with initial pH of 5 and temperature of 28OC. Pineapple peel was used as the substrate after romoving water content using ammonium dihydrogen phosphate. Cell growth was analyzed by calculating the total of microorganism cell using hemocytometer. In order to determine lactate acid production, glucose concentration was analyzed using spectrophotometer. Nelson-Somogy method was employed in this analysis. Ethanol concentration was also analyzed by calculating the titration of acid lactate concentration. The optimum growth of Lactobacillus plantarum was found at 28oC, stirring rate of 150 rpm and substrate concentration of 500 g/L contributing to the total cell of 3,85.108, 1,13.109, and 4,00.108 for lag, exponential, and decrease phase respectively. Further analysis carried out based on stirring rate of 150 rpm and substrate concentration of 500 g/L resulted in the largest average concentration of lactate acid of 1.620% v/v with glucose consumption percentage of 51,76%.Keywords: pineapple peel, Lactobacillus plantarum, lactate acid